Transformational School Leadership for Technology-Based Education: A Multi-Case Study Supporting SDG 4 - Yohanes Eko Prasetyo Prasetyo; Yatim Riyanto; Nunuk Hariyati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examines the role of transformational leadership in managing technology-based vocational schools and its contribution to improving educational quality through digital transformation. Method: A qualitative multi-case study was conducted at SMK Mitra Sehat Sidoarjo and SMKN 1 Sidoarjo. Data were collected through interviews, observations, and document analysis, and analyzed using thematic analysis to identify leadership practices supporting technology integration. Results: The findings indicate that transformational school principals successfully promoted technology integration by fostering a shared vision, encouraging innovation, strengthening teacher professional development, and implementing collaborative and data-driven school management. These leadership practices enhanced digital learning, organizational effectiveness, and the quality of educational services despite challenges related to infrastructure and digital competencies. Novelty: Proposing a transformational leadership framework for technology-based vocational school management that integrates digital innovation with collaborative leadership practices. The framework contributes to SDG 4 (Quality Education) by improving the quality and inclusiveness of technology-enhanced education and supports SDG 9 (Industry, Innovation and Infrastructure) by strengthening digital innovation and institutional capacity for sustainable educational transformation.